2017
DOI: 10.21276/ijlssr.2017.3.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Nanoparticle Enhanced Photodynamic Therapy against Biofilm forming Streptococcus mutans

Abstract: ABSTRACT-Present work explores the novel selenium nanoparticle-enhanced photodynamic therapy of toluidine blue O against Streptococcus mutans biofilm. Physiochemical (Ultraviolet-visible absorption, FTIR, and fluorescence spectroscopy) and Electron microscopy techniques were used to characterize selenium nanoparticles. The UV spectrum of different concentrations of SeNP were showed distinct peak at ~288 nm, which confirmed the successful synthesis of SeNP in this study. The synthesized Selenium nanoparticles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This result was in agreement with the study conducted by Haris et al that assessed the effect of the combination of TBO-induced PDT and SeNPs on the S. mutans biofilm. Also, their results revealed that SeNPs increased the anti-biofilm effect of PDT [ 6 ]. In another study, the effect of TBO-induced combined with silver nanoparticles (TBO-AgNPs ) has been evaluated on the S. mutans biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was in agreement with the study conducted by Haris et al that assessed the effect of the combination of TBO-induced PDT and SeNPs on the S. mutans biofilm. Also, their results revealed that SeNPs increased the anti-biofilm effect of PDT [ 6 ]. In another study, the effect of TBO-induced combined with silver nanoparticles (TBO-AgNPs ) has been evaluated on the S. mutans biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these techniques (e.g., the mechanical disruption of oral biofilms or the use of therapeutic antimicrobials in the oral cavity) are subjected to several restrictions [ 5 ]. In this regard, alternative antibacterial strategies (e.g., photodynamic therapy (PDT)) are employed to control microbial growth in the oral cavity [ 6 ]. PDT has three principle nontoxic components, including visible light, a photosensitizer (PS), and molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study presented the synthesis of pristine and metalloid-doped metal-oxide NPs and their effectiveness as antimicrobial nanofillers in composite resins. The metalloid selected for doping was Se, based on its antioxidant, antiviral, anti-inflammatory, and antibacterial properties [ 33 ]. The synthesis of pristine and doped NPs was confirmed by several characterization techniques used with NPs, i.e., UV-Vis spectroscopy, XRD crystallography, FTIR analysis, SEM, and EDX analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Stable-liquid interface is the primary intent for their attachment (Graham and Cady, 2014). Exclusive motive at the gain of the attachment of microbes is floor hydrophobicity due to the fact that it substantially reduces pressure of repulsion between microorganism and floor (Haris & Khan, 2017;Kumaran et al, 2018). Microorganisms have a greater capacity to cling to Teflon or plastics because they are hydrophobic and non-polar surfaces, as opposed to metals or glass, which are polar and hydrophilic (Li et al, 2017;Mao et al, 2017;Misba et al, 2018).…”
Section: Initial Contact or Attachment To The Surfacementioning
confidence: 99%